Vocational School Students' Vocational Identity and Their Views on the Functions of School - Cheng-Yen Shih; Chia-Ling Chiang (National Taipei University of Education, 2016)
This study aims to explore the students' viewpoints on the functions of vocational schools, as well as the connection between their vocational identity and their opinions on the functions of schools. After understanding the students' views of the practical support their schools have provided, the curricula and learning goals of vocational schools were reexamined. Ten in-service vocational school students, between the ages of 18-22, were invited to participate in this study. Each student was interviewed individually by the researchers for approximately 60 minutes and they were asked to use mind maps to express their viewpoints. The results showed that students regarded the vocational school as a means to obtain diplomas and professional licenses, a place to get to know friends, and a place to escape from the pressures of reality. Students with higher vocational commitment tended to care about their careers more deeply. In order to obtain a degree or professional licenses, a higher salary, and greater self-affirmation, these students actively engaged in learning. Students with lower vocational commitment tended to be in the stage of career exploration as they kept searching for career goals. They were confused by their current jobs and with the school curriculum; however, when an identified career role model or a hopeful vision was demonstrated to them, some students with lower vocational commitment would be stimulated to gain a positive career motivation and expressed the flexibility to have a career/life change.